On Credentials - Giuseppe Lorini (Journal of Social Ontology, 2022)
Credentials play an important role in all modern societies, but the analysis of their nature and function has thus far been neglected by social philosophers. We present a view according to which the defining function of credentials is to certify the identity and the institutional status (including certain rights) of individuals. More importantly, credentials enable rights-holders to exercise their rights, so that for a particular right to be exercisable the right-holder should possess, carry and sometimes show to an authority a document of a specific kind. Driving licenses, identity cards, passports, boarding passes, library passes, credit cards, ATM cards, health insurance cards are all examples of credentials in this sense. Credentials have in every case a bearer, and the bearer should be able to carry them easily on his or her person. Credentials should also be inspectable – not least because credentials can be forged. The authors analyze several historical and contemporary examples of credentials, focusing on the credentials carried by the pilgrims of the Way of Saint James.